The effect of formative assessment on high school students' mathematics achievement and attitudes - Yusuf Ziya Kültür; Mahmut Oğuz Kutlu (Journal of Pedagogical Research, 2021)
The purpose of this research is to examine the effects of formative assessment practices on students' academic achievement, attitudes towards mathematics, and to investigate their views on formative assessment practices. A 12-week quasi-experimental research design was adopted in the research. The research group consisted of 51 students in the 10th grade (26 in the experimental group and 25 in the control group) of a high school. Qualitative data were obtained via functions academic test and mathematics attitude scale while a semi-structured interview form was used as a qualitative data collection tool. The quantitative results revealed that the effect of formative assessment practices on students' attitudes towards mathematics and mathematics achievement was statistically significant. According to the qualitative results of the research, formative assessment practices were found to be beneficial in terms of contributing to learning processes and encouraging students to express themselves in the classroom. It is recommended that teachers use formative assessment to support student-centered classrooms in teaching mathematics and to effectively evaluate students' mathematical competence in the learning process.